Integrated Nutrient Management for Sunflower in Coastal Char Land of Bangladesh - Farhad, ISM; Jahan, E; Anik, MFA; Chowdhury, MMU; Akter, S (Bangladesh Agronomy Journal, 2020)
An experiment was conducted at coastal charlandof OFRD, BARI, Noakhali;MLT site, Amtoli,Bargunaand ARS,Benarpota, Satkhira during Rabi season of 2018-19to evaluate the effect of integrated nutrient management on growth,yield and economic performance of sunflower. Six treatment combinations viz. T1= Soil test based fertilizer dose for HYG, T2 = IPNS with 5 tha-1cowdung, T3= IPNS with 5 tha-1 compost, T4= IPNS with 1.5 t ha- 1vermicompost, T5= Farmers’ practice and T6= Absolute control were tested. The experiment was laid out in a randomized complete block design with 3 replications and BARI Sunflower-2 was used as test crop.The IPNS treatment combinations are significantly differentfrom rest of the treatments in terms of yield and economic return. Application of treatment IPNS with 1.5 tha-1vermicompost significantly increased all of the parameters such as the plant height, head diameter, number of seed per head,1000 seed weight, seed yield and stover yield. The significantly highest seed yield (2.19, 2.23 and 2.06 t ha-1 at Noakhali, Bargunaand Satkhira, respectively) was recorded in IPNS with 1.5 tha-1vermicompost treated plot (T4) while the lowest seed yield (1.05, 1.10 and 1.02 t ha-1 at Noakhali, Barguna and Satkhira, respectively) was observed in absolute control treatment (T6). Salinity level increased at slower rate in T2, T3 and T4, treatments where IPNS based nutrient management packages were imposed.During the crop growing period soil salinity ranged from 0.62 to 9.72dS m-1, 0.58 to 9.23dS m-1, 0.73 to 9.86dS m-1 at Noakhali, Barguna and Satkhira, respectively from emergence to maturity stages of the crop. The highest net return (50790 Tk. ha-1, 52765 Tk. ha-1 and 43940 Tk. ha-1 at Noakhali, Barguna and Satkhira, respectively) as well as BCR (1.75, 1.78 and 1.67 atNoakhali, Barguna and Satkhira, respectively) were obtained from T4 treatment (IPNS with 1.5 tha-1vermicompost) whereas the lowest net return (14900 Tk. ha-1 ,15175 Tk. ha-1 and 11570 Tk. ha-1 at Noakhali, Barguna and Satkhira, respectively) and BCR (1.40, 1.33 and 1.26at Noakhali, Barguna and Satkhira, respectively) were obtained from control (T6) treatment. The overall results indicated that IPNS with 1.5 tha-1 vermicompostis more effective than other fertilizer management packages in respect of yield as well as economic return for sunflower cultivation in the coastal charland of Bangladesh. Bangladesh Agron. J. 2019, 22(2): 151-159